Sustaining education through mobile learning using pocket education(PE®). - Ismail, Issham
The project aimed to identify the potential of SMS-based m-Iearning in supporting various fields of study which is divided into five groups.The first group examined the level of awareness on m-Iearning pedagogy, surveyed to 551 university students from 11 IPTA in Malaysia and reported that the respondents were generally undecided and lack of knowledge on how m-learning is useful for learning. Second project related to the development of SMS-based mlearning system, namely Pocket Education (PE®), utilized as the core system to supporting various research applications, including UniPE.